2014
DOI: 10.3389/fimmu.2014.00033
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis Using High Definition Flow Cytometry Reveals Distinct T Cell Repertoires between the Fetal–Maternal Interface and the Peripheral Blood

Abstract: The human T cell compartment is a complex system and while some information is known on repertoire composition and dynamics in the peripheral blood, little is known about repertoire composition at different anatomical sites. Here, we determine the T cell receptor beta variable (TRBV) repertoire at the decidua and compare it with the peripheral blood during normal pregnancy and pre-eclampsia. We found total T cell subset disparity of up to 58% between sites, including large signature TRBV expansions unique to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…However, there is compelling data suggesting that changes in percentages of Treg cells within CD4 + cells play a central role in many immune-mediated pathologies 4043 . In line with this, our own group has shown reduced percentages in maternal Tregs to be a feature of altered immunity in preeclampsia 4,44,45 . Hence, differences in percentages of offspring Treg cells described in this study between the preeclampsia and non-preeclampsia groups seems highly relevant.…”
Section: Discussionsupporting
confidence: 62%
“…However, there is compelling data suggesting that changes in percentages of Treg cells within CD4 + cells play a central role in many immune-mediated pathologies 4043 . In line with this, our own group has shown reduced percentages in maternal Tregs to be a feature of altered immunity in preeclampsia 4,44,45 . Hence, differences in percentages of offspring Treg cells described in this study between the preeclampsia and non-preeclampsia groups seems highly relevant.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, the repertoire of effector Treg cells of PBMC was not skewed in the 3rd trimester. A previous study showed that TRBV repertoires of total Treg cells differ in PBMC and decidua in the 3rd trimester ( 22 ). Our data support this finding.…”
Section: Discussionmentioning
confidence: 99%
“…T cell receptor β variable (TRBV) repertoires of total Treg cells in peripheral blood and decidua were not significantly different between preeclampsia and normal pregnancy (22). Thus, how Treg cells relate to the development of preeclampsia remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on decidua tissue taken from term placenta samples show that Tregs undergo clonal expansion throughout pregnancy, of note this cannot be detected in the peripheral blood Treg ( 26), but peripheral blood Treg numbers increase in human pregnancies as gestation progresses. Our observation that the CD4Tconv compartment is similar between the PB and endometrium, whereas Treg have greater significant phenotypic differences, suggests Treg tissue specificity, this was observed by a study analysing the T cell receptor beta variable (TRBV) repertoire that found most variation in the Treg population between cells derived from the blood or decidua (27). IFN was identified as the most upregulated gene in Treg from parous women.…”
Section: Discussionmentioning
confidence: 56%